Penerapan Metode PSI dalam Pendukung Keputusan Kelayakan Nasabah Penerima Pinjaman - Dito Putro Utomo; Raheliya Br Ginting (JISTI: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2026)
PT. Permodalan Nasional Madani (Persero) or abbreviated as PNM Mekaar is an Indonesian State-Owned Enterprise which operates in the financial services sector. PNM Mekaar is a service provided by PT Permodalan Nasional Madani (PNM) whose main objective is to provide loan financing to female entrepreneurs engaged in Micro, Small and Medium Enterprises. The aim is to help these entrepreneurs increase their income and improve their economic well-being and provide them with access to finance, business and financial education. The loan limit offered by PNM Mekaar Bank starts from IDR 2,000,000 and continues to increase to IDR 5,000,000 for ordinary loans. The PNM Mekaar Plus loan term ranges from IDR 15,000,000 to IDR 25,000. 000 depending on the limit. The research framework is related to the Decision Support System in selecting customers who are eligible to receive loans at BANK PNM Mekaar Lubuk Pakam Branch by applying the SPK Preference Selection Index method. From the table above it is stated that the alternative with C8 has the highest value with a value of 0.222403657 and is followed by alternative code A7 with a value of 0.207720657. This research aims to determine the determination of customers who are eligible to receive loans at Bank PNM Mekaar which aims to provide loan financing to women entrepreneurs operating in the Small and Medium Enterprises sector.